Sosialisasi Pencegahan Perundungan di Sekolah Dasar Negeri Seumantok Kabupaten Aceh Barat - Sopar, Sopar; Saputra, Akmal; Yulianda, Riki; Abdillah, Ligar; Sarianti, Lilis; Arfriani, Arfriani (Medan Resource Center, 2024)
Bullying in elementary schools is a common issue that can negatively impact children's psychological, social, and academic development. Therefore, preventive efforts through socialization activities are necessary to raise awareness and understanding among students, teachers, and parents regarding bullying prevention. This community service was carried out at Seumantok Public Elementary School, West Aceh Regency, aiming to provide education on the effects of bullying and strategies for its prevention. The methods used included interactive presentations, group discussions, and bullying scenario simulations to provide participants with a comprehensive understanding. The results showed that this socialization successfully increased students' awareness of the importance of mutual respect and the adverse effects of bullying. Teachers were also trained to recognize signs of bullying and implement strategies to manage classroom conflicts. Additionally, parents were provided with guidance on creating a family environment that supports children's emotional development. Program evaluation through surveys indicated that 85% of participants felt more prepared to prevent and handle bullying cases. This community service concludes that an education-based approach, collaboration, and the involvement of all stakeholders effectively raise awareness and foster an anti-bullying culture in elementary schools. Similar programs are recommended to be implemented in other schools as part of efforts to create a safe and conducive learning environment.